2020
DOI: 10.3389/fonc.2020.01017
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Delta-Radiomics Better Differentiate Pre-Invasive GGNs From Invasive GGNs?

Abstract: Purpose: This study aimed to explore the role of delta-radiomics in differentiating pre-invasive ground-glass nodules (GGNs) from invasive GGNs, compared with radiomics signature. Materials and Methods: A total of 464 patients including 107 pre-invasive GGNs and 357 invasive GGNs were embraced in radiomics signature analysis. 3D regions of interest (ROIs) were contoured with ITK software. By means of ANOVA/MW, correlation analysis, and LASSO, the optimal radiomic features wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Delta-radiomics is a subspecialty of radiomics that studies the variations of the radiomic features in time [ 5 ] or after the introduction of an external agent either pharmacologic (chemotherapy, immunotherapy) or physical (radiotherapy) to produce biomarkers able to describe or predict a specific clinical situation (i.e., response, early recurrence). Delta-radiomics does not depict a static situation, but its evolution; confronting delta-radiomic features means comparing different starting situations that present similar changes.…”
Section: Introductionmentioning
confidence: 99%
“…Delta-radiomics is a subspecialty of radiomics that studies the variations of the radiomic features in time [ 5 ] or after the introduction of an external agent either pharmacologic (chemotherapy, immunotherapy) or physical (radiotherapy) to produce biomarkers able to describe or predict a specific clinical situation (i.e., response, early recurrence). Delta-radiomics does not depict a static situation, but its evolution; confronting delta-radiomic features means comparing different starting situations that present similar changes.…”
Section: Introductionmentioning
confidence: 99%
“…We should think highly of DWI due to its potential for evaluating DR and non-DR in clinical practice. As has been investigated that delta-radiomics analysis explored the change of radiomics features between baseline and follow-up computed tomography images can improve the differentiation of pre-invasive ground glass nodules from invasive ground glass nodules[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics has the potential to provide quantitative information of tumor heterogeneity by converting images into mineable data, 7 regarding histogram, texture, form factor, gray level co-occurrence matrix (GLCM), gray level run-length matrix (GLRLM), and gray level size zone matrix (GLSZM). 8 The radiomics signature has been of great interest over the last several years to diagnose fp-AML. 9 Previous publications reported that CT-based radiomics signature demonstrated better performance in distinguishing fp-AMLs from ccRCCs.…”
Section: Introductionmentioning
confidence: 99%